Investigating Ferroresonance Phenomenon in a Single-Phase Transformer with the Effect of Magnetic Hysteresis - Behrooz Rezaeealam; Behzad Norouzi (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
Ferroresonance is a non-linear phenomenon and very dynamic in the power quality problems. This phenomenon should be carefully analyzed so that preventive measures could be taken before its appearance and prevent injury and damage to electrical power appliances. Ferroresonance is seen more in the middle-voltage networks with supplying unloaded or slightly loaded transformers by cables. The materials used in the manufacture of transformer cores are creates a major role in their dynamic behavior. In this article are used from two types magnetic material GOES and NGOES in the transformer core of single phase. The physical behavior of these materials is considered during the core hysteresis. For modeling the hysteresis loop has been used from Jiles-Atherton method. By using the finite element method and with help COMSOL Multiphysics Software, transformer is simulated in two space dimensions. Laboratory test the transformer core hysteresis loop is described and shows which the Jiles-Atherton model is one of the best known models of hysteresis. The results shows which use of GOES materials in the transformer core is cause Significant reduction the core losses in comparison with the NGOES materials. Also change of ferroresonance mode and the severity its occurrence are the results of changing the material used in the transformer core.